The effect of the dimensions of the strategic lens on achieving tax pioneer performance: Practical research in the General Authority for Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The aim of the research is to shed light on the dimensions of the strategic lens and its impact on achieving the pioneer tax performance and represented by the dimensions (strategic direction, growth, pilot indicator, renewal and modernization, efficiency and effectiveness) in the General Tax Authority. The questionnaire was adopted as a tool to collect data and information from the adult sample They are (91) who are on the site (Assistant Director General, Head of Division, First Division Deputy, Second Division Deputy, Division Officer, Division Officer Associate) The statistical program (SPSS) has been used to calculate (the mean, the standard deviation, the correlation coefficient, the difference coefficient, the F test, the R2 parameters, the X2 test, the T test), and the research reached a number of conclusions, the most prominent of which were: - 1-There is an effect The strategic lens in the dimensions of entrepreneurial tax performance, 2 - There are significant differences in the response of the sample about the questionnaire paragraphs in personal variables (career level, scientific location, number of years of service).